Utilization Of Digital Technology As A Strategy For Empowering Micro Business In Parepare City - Aqhzira Aulia Muhtar; Nuringsih; Kurniati Yunus (www.amertainstitute.com, 2024)
This study aims to analyze the use of digital technology as a strategy for empowering micro-enterprises in Parepare City. In facing increasingly tight competition, micro-enterprises need innovative strategies to increase competitiveness and operational efficiency. The use of digital technology, such as social media, e-commerce platforms, and financial applications is considered an effective effort to support the development of micro-enterprises. The type of research used is qualitative research that explains phenomena and perceptions. While the type of approach used by researchers is descriptive data in the form of in-depth interviews with micro-economic actors, field observations and literature studies. The research results obtained are: increasing market access in terms of digital technology in this case e-commerce and social media, provides opportunities for micro businesses to expand market networks for Micro Business actors in Parepare City who previously only relied on traditional markets but can now reach consumers from various regions. Then the perception of Micro business actors regarding the implementation of strategies that a strategy is very important in trying because with a strategy Micro Business actors can anticipate something bad that will happen in the future.